International criminal procedure - Boas, Gideon (Cambridge ; New York : Cambridge University Press, 2011)
"The third volume in the series examines international criminal proc edure as set out in the regulatory provisions and jurisprudence of the international criminal tribunals. It reviews in detail the key areas of international criminal procedure, including the relationship between t he international tribunals and national jurisdictions, investigations, pre-trial and trial proceedings, the rules of evidence, representation of accused, the role and status of victims, judgments, and the appeals process. Moreover, the volume also considers the legal foundations and sources of this area of the law, the rule-making and amending powers of the international tribunals, and the structure of the administrative d ecision-making processes that impact upon crucial areas of the substant ive law. In providing a thorough and critical overview of the mechanics of investigating and trying international crimes, International Crimin al Procedure will complement the first two volumes in the series, and t hus complete a comprehensive work on international criminal law"--
"Volume 3 of the International Criminal Law Practitioner Library com pletes the review of international criminal law begun in Volumes 1 and 2, which analyse the forms of responsibility and the elements of the co re crimes. This volume reviews the procedural law and practices of the international criminal tribunals from investigation to trial, appeal, a nd punishment, and examines the framework within which the substantive law operates. The authors present a critical study of those procedures that are essential to effective investigations and fair trials, and exp lore how the ICC, ICTY, and ICTR - as well as the SCSL and other intern ationalised tribunals, where relevant - have shaped the evolution of in ternational criminal procedure in order to meet new challenges and chan ging circumstances. The key jurisprudence and rule amendments up to 1 D ecember 2009 have been surveyed, making this a highly relevant and time ly work"--
Machine generated contents note: 1. The nature of international crim inal procedure; 2. Creation and amendment of rules of international cri minal procedure; 3. Procedures related to primacy and complementarity; 4. Investigations, rights of suspects, and detention; 5. Defence counse l, amici curiae, and the different forms of representation of accused; 6. Pre-trial proceedings; 7. Trial proceedings; 8. The role and status of victims in international criminal procedure; 9. Evidence; 10. Judgem ent and sentencing; 11. Appeal and revision; 12. Conclusion.
Includes bibliographical references and index.
Keywords: International criminal courts -- Rules and practice; Criminal procedure (International law); Criminal justice, Administration of; Complementarity (International law)